2017
DOI: 10.3390/s17061233
|View full text |Cite
|
Sign up to set email alerts
|

Performance of BDS-3: Measurement Quality Analysis, Precise Orbit and Clock Determination

Abstract: Since 2015, China has successfully launched five experimental BeiDou global navigation system (BDS-3) satellites for expanding the regional system to global coverage. An initial performance assessment and characterization analysis of the BDS-3 is presented. Twenty days of tracking data have been collected from eleven monitoring stations. The tracking characteristics and measurement quality are analyzed and compared with the regional BDS (BDS-2) in terms of observed carrier-to-noise density ratio, pseudo-range … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(29 citation statements)
references
References 24 publications
0
29
0
Order By: Relevance
“…Tan et al showed the initial results of the precise orbit determination with nine stations [10]. Xie et al evaluated the multipath effect and the performance of the precise orbit and clock determination [11]. Zhao, et al proved that the best orbit determination solution for BeiDou-3e is obtained with five-parameter Extended CODE Orbit Model (ECOM) and a three-day arc [12].…”
Section: Introductionmentioning
confidence: 99%
“…Tan et al showed the initial results of the precise orbit determination with nine stations [10]. Xie et al evaluated the multipath effect and the performance of the precise orbit and clock determination [11]. Zhao, et al proved that the best orbit determination solution for BeiDou-3e is obtained with five-parameter Extended CODE Orbit Model (ECOM) and a three-day arc [12].…”
Section: Introductionmentioning
confidence: 99%
“…System) are widely used for navigation, positioning, scientific [1][2][3][4], and engineering applications [5][6][7]. That includes deformations [8][9][10] and structure monitoring [11][12][13], GIS (Geographic Information System) applications [14][15][16], land use [16][17][18][19], and cadastre [20][21][22][23][24].…”
Section: Gnss (Global Navigationmentioning
confidence: 99%
“…The BDS-3 starts its development with a five experimental satellites demonstration system since 2015, including two IGSO satellites, I1-S (C31) and I2-S (C32), and three MEO satellites, M1-S (C33), M2-S (C34) and M3-S (C35) (Xie et al 2017;Yang et al 2018). The goal of this demonstration system is to comprehensively test and analyze its new features, e.g., the new types of the navigation signals, the inter-satellite links (ISL), and the uploading injection and downloading reception signal, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Though the number of stations is rather limited, Tan et al (2016) presented the first attempt of precise orbit determination (POD) for the experimental satellites with the old B1, B2 and B3 signals. Xie et al (2017) presents the POD results with the new navigation signals, and the orbit overlap and the satellite laser ranging (SLR) evaluation both suggested that the POD precision is about 2-6 dm in 3D and 1-2 dm in the radial component. As a great advantage of the new generation BDS, the contribution of the ISL in terms of POD was analyzed and confirmed by Ren et al (2017) with different data processing strategies.…”
Section: Introductionmentioning
confidence: 99%